Don's Motivation for Speech in Jumbo Animated Films: A Psycholinguistic Study - Putri, Sandrina Febiola; Eko Muharudin; Eko Suroso; Sukirno (Universitas Cokroaminoto Palopo, 2026)
Speech motivation in animated films is generally influenced by the emotional dynamics and psychological needs of the characters involved in a particular speech situation. The relationship between internal drives, affective conditions, and language realization has not been fully understood in animated film studies, especially from a psycholinguistic perspective. This study aims to identify and describe the forms of speech motivation of the character Don in the animated film Jumbo (2025) through a psycholinguistic approach supported by pragmatic context analysis. The issues examined in this study are how Don's emotional state and psychological needs become dominant factors in shaping the construction of speech motivation and how this circular pattern of motivation works in speech dynamics. This study uses a qualitative descriptive method with a psycholinguistic approach. The research data consists of quotes from Don's dialogue that contain indications of speech motivation in the film. The data collection technique was carried out through listening and note-taking, while the data analysis technique used an interactive analysis model that included data reduction, data presentation, and verification and conclusion drawing. The research findings were then integrated into a contextual circular model of speech motivation as a conceptual analysis tool to map the relationship between situational stimuli, emotions, psychological needs, communicative goals, and social responses. The results showed that Don's speech motivation was dominated by the needs for belonging and recognition, which emerged through various emotional conditions such as happiness, fear, anger, disappointment, regret, and longing. Each utterance is formed through a circular process involving external stimuli, cognitive evaluation, activation of psychological needs, and linguistic realization in the form of verbal and nonverbal expressions. The circular model of speech motivation formulated in this study shows that speech is the result of psychological drives and becomes an evaluative mechanism that re-influences the